FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Christa Evandini; Darsono Darsono (Diponegoro Journal of Accounting, 2014)
This study aims to analyzed the factors that influence CSR disclosure in annual reports companies listed in Indonesia Stock Exchange ( IDX ) . CSR is the practices of the company to meet the expectations of the public , thus creating public legitimacy for the existence of the company . The examined factors are profitability , board size , public ownership , firm size , leverage , and growth of the company as an independent variable while CSR disclosure as the dependent variable .         The data used in this study are secondary data and selection of samples using purposive sampling method . The method used to measure CSR disclosure is the content analysis . The measurement method of content analysis is done by providing a checklist on the items of the financial statements of CSR in the company's annual report. Sample consisted of 223 companies that listed in Indonesia Stock Exchange ( BEI ) in the period 2009-2012 . Model analysis for this study using multiple linear regression analysis .         Based on the analysis results of the study showed that the only variable board size , firm size, leverage significantly affect the disclosure of CSR , while the variable profitability , public ownership , the growth of the company does not have a significant influence on the disclosure of CSR companies listed on the Stock Exchange .